1987
DOI: 10.1177/0164027587094004
|View full text |Cite
|
Sign up to set email alerts
|

Retirement as a Critical Life Event

Abstract: This article examines the experience of adaptation to retirement among a sample of women (n = 124) and men (n = 176) retired an average of three years and living in an urban area of Ontario, Canada. The impact of retirement as a life event relative to other life experiences was examined, and found to be distinctly less critical than previous research would suggest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 43 publications
0
22
0
2
Order By: Relevance
“…The decision to retire is complex and entails much more than just a decision to stop working full-time (Reitzes, Mutran, and Fernandez, 1998). Research on retirement over the past decades has found that most retirees look forward to retirement, are happy with this time and suffer no ill-effects as a result of labor force withdrawal (Beck, 1992;Ekerdt, 1987;Ekerdt and Bosse, 1982;Martin Matthews and Brown, 1987;Sacombee and Lee, 1986). Atchley (1982) found that while activity levels were important for men and women retirees, the similarity ended after that.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to retire is complex and entails much more than just a decision to stop working full-time (Reitzes, Mutran, and Fernandez, 1998). Research on retirement over the past decades has found that most retirees look forward to retirement, are happy with this time and suffer no ill-effects as a result of labor force withdrawal (Beck, 1992;Ekerdt, 1987;Ekerdt and Bosse, 1982;Martin Matthews and Brown, 1987;Sacombee and Lee, 1986). Atchley (1982) found that while activity levels were important for men and women retirees, the similarity ended after that.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For women, good health and older age were predictive of life satisfaction during retirement, whereas having an adequate income and many goals were important for men. Martin Matthews and Brown (1987) found occupational factors and health to be important for men's morale, while only health had an influence on women. In contrast Sacombee and Lee (1986) found health, marital status, and income to be predictors of satisfaction for both men and women.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Differences in adaptation to retirement may be related to the differ ences of individuals' earlier development and their actual life situation: The meaning of retirement differs from one individual to another. An important task for research is, thus, to delineate the characteristics of indi viduals, and the specific conditions of retire ment, associated with problems in adjust ment to retirement [6,7], Many studies dealing with the effects of retirement have been retrospective and cross-sectional and often have not included any control group. These kinds of study de signs are particularly problematic if the aim is to analyze changes probably caused by retirement from employment.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers rely on general adjustment measures such as life satisfaction or morale (Dorfman, Kohout, & Heckert, 1985; Matthews & Brown, 1987). Such measures may not adequately capture adaptation to the retirement transition.…”
Section: Methodsmentioning
confidence: 99%